2021
DOI: 10.3389/fpls.2021.701683
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Functional Subdomains in the atALKBH9B m6A-Demethylase Required for Its Binding to the Viral RNA and to the Coat Protein of Alfalfa Mosaic Virus

Abstract: N6-methyladenosine (m6A) modification is a dynamically regulated RNA modification that impacts many cellular processes and pathways. This epitranscriptomic methylation relies on the participation of RNA methyltransferases (referred to as “writers”) and demethylases (referred to as “erasers”), respectively. We previously demonstrated that the Arabidopsis thaliana protein atALKBH9B showed m6A-demethylase activity and interacted with the coat protein (CP) of alfalfa mosaic virus (AMV), causing a profound impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 90 publications
(124 reference statements)
1
21
0
Order By: Relevance
“…This ORF contains a 2-ODD domain, conserves the cofactor-binding residues necessary for its activity (Figure 4B), is most closely related to known RNA demethylases from human and Arabidopsis (Figure 4A) and, most importantly, the purified protein shows RNA demethylase activity in vitro (Figure 5) and capability to bind RNA (Figure 6). Interestingly, the apparent constant dissociation (Kd) calculated for the paALKBH5-like protein (0.21 µM, Figure 6) was similar to that observed for atALKBH9B (0.30 µM) (Alvarado-Marchena et al, 2021) reinforcing the notion that both proteins are functionally equivalent.…”
Section: Discussionsupporting
confidence: 70%
“…This ORF contains a 2-ODD domain, conserves the cofactor-binding residues necessary for its activity (Figure 4B), is most closely related to known RNA demethylases from human and Arabidopsis (Figure 4A) and, most importantly, the purified protein shows RNA demethylase activity in vitro (Figure 5) and capability to bind RNA (Figure 6). Interestingly, the apparent constant dissociation (Kd) calculated for the paALKBH5-like protein (0.21 µM, Figure 6) was similar to that observed for atALKBH9B (0.30 µM) (Alvarado-Marchena et al, 2021) reinforcing the notion that both proteins are functionally equivalent.…”
Section: Discussionsupporting
confidence: 70%
“…Using the online tool Clustal Omega, we obtained the alignment between the amino acid sequences of the AlkB domain (residues 222 to 412 in ALKBH9B) from these three proteins and human ALKBH5 (hsALKBH5, residues 85 to 284; Figure 1A ). Remarkably, the AlkB domain and some amino acids described as key residues for the m 6 A demethylation activity of hsALKBH5 (highlighted in Figure 1A ) are quite conserved in the three ALKBH9 Arabidopsis co-orthologues ( Feng et al, 2014 ; Lu et al, 2014 ; Alvarado-Marchena et al, 2021 ). Thus, we observed that the known HxD/E·· H and RxxxxxR motifs are conserved between the three proteins ( Figure 1A , highlighted in yellow).…”
Section: Resultsmentioning
confidence: 98%
“…In previous work, we found that the AMV CP interacts with ALKBH9B and we showed that this protein decreases m 6 A relative abundance along AMV vRNAs. In turn, this promotes viral accumulation in Arabidopsis since the virus showed an impaired systemic invasion capability in alkbh9b plants ( Martínez-Pérez et al, 2017 ; Alvarado-Marchena et al, 2021 ). Here, we discard that the other ALKBH9 close paralogous proteins affect AMV infection and we make a deep analysis of the infection restriction observed in alkbh9b plants.…”
Section: Introductionmentioning
confidence: 99%
“…Further to the control at DNA or chromatin level, we suggest that an epitranscriptomic mark adds to the complex regulation of gene expression variability. Given that m 6 A-methylated mRNAs are preferably located to cytoplasmic stress granules (SGs) (Alvarado-Marchena et al, 2021; Fu and Zhuang, 2020; Ries et al, 2019; Scutenaire et al, 2018), we speculate that the physical confinement of m 6 A-methylated transcripts to SGs might play a role in stable gene expression variability. To test this possibility, we compared LVGs and random genes for their SG enrichment score determined in our previous study (Kim et al, 2021), and LVGs indeed showed stronger SG enrichment (Fig.…”
Section: Discussionmentioning
confidence: 99%